Karakteristik Belajar Siswa Gaya Belajar Siswa dan Pendekatan Individual dalam Pengajaran Rasulullah - Siti Aisyatunnadiya; Putri Talia; Fatimatuzzahra Fatimatuzzahra (STAI Al-Hamidiyah Jakarta, 2026)
In the modern era, the primary challenge in Islamic Education (PAI) is the stagnation of conventional teaching methods that utilize a